Association between Ischemic Electrocardiographic Changes during Acetylcholine Provocation Test and Long-Term Clinical Outcomes in Patients with Vasospastic Angina - Im, Sung Il; Rha, Seung-Woon; Choi, Byoung Geol; Choi, Cheol Ung; Lim, Hong Euy; Kim, Jin Won; Kim, Eung Ju; Park, Chang Gyu; Seo, Hong Seog (Kosin Medical Journal (Online), 2019)
Objectives Intracoronary injection of acetylcholine (Ach) has been shown to induce significant coronary artery spasm (CAS) in patients with vasospastic angina. Clinical significance and angiographic characteristics of patients with ischemic electrocardiogram (ECG) changes during the Ach provocation test are not clarified yet. Methods A total 4,418 consecutive patients underwent coronary angiography with Ach provocation tests from 2004 to 2012 were enrolled. Ischemic ECG changes were defined as transient ST-segment depression or elevation ( > 1 mm) and T inversion with/without chest pain. Finally, a total 2,293 patients (28.5% of total subjects) proven CAS were enrolled for this study. Results A total 119 patients (5.2%) showed ECG changes during Ach provocation tests. The baseline clinical and procedural characteristics are well balanced between the two groups. Ischemic ECG change group showed more frequent chest pain, higher incidence of baseline spasm, severe vasospasm, multi-vessel involvement, and more diffuse spasm ( > 30 mm) than those without ischemic ECG changes. At 5 years, the incidences of death, major adverse cardiac events (MACE) and major adverse cardiac and cerebral events (MACCE) were higher in the ischemic ECG change group despite of optimal medical therapy. Conclusions The patients with ischemic ECG changes during Ach provocation tests were associated with more frequent chest pain, baseline spasm, diffuse, severe and multi-vessel spasm than patients without ischemic ECG changes. At 5-years, the incidences of death, MACE and MACCE were higher in the ischemic ECG change group, suggesting more intensive medical therapy with close clinical follow up will be required.